1999
DOI: 10.1212/wnl.52.3.629
|View full text |Cite
|
Sign up to set email alerts
|

Plasma exchange versus intravenous immunoglobulin treatment in myasthenic crisis

Abstract: We performed a retrospective multicenter chart review to compare the efficacy and tolerance of plasma exchange (PE) and intravenous immunoglobulin (i.v.Ig) in treatment of 54 episodes of myasthenic crisis. After adjustment for other variables, PE (compared with i.v.Ig) was associated with a superior ventilatory status at 2 weeks (partial F = 6.2, p = 0.02) and 1 month functional outcome (partial F = 4.5, p = 0.04). However, the complication rate was higher with PE compared with i.v.Ig (13 versus 5 episodes, p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
0
7

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(126 citation statements)
references
References 7 publications
3
111
0
7
Order By: Relevance
“…Patients often qualify for thymectomy, which improves the prognosis and long-term treatment outcomes [5,8,9]. The histopathological examinations usually reveal thymus hyperplasia; thymoma is observed less frequently [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients often qualify for thymectomy, which improves the prognosis and long-term treatment outcomes [5,8,9]. The histopathological examinations usually reveal thymus hyperplasia; thymoma is observed less frequently [9].…”
Section: Discussionmentioning
confidence: 99%
“…The histopathological examinations usually reveal thymus hyperplasia; thymoma is observed less frequently [9]. To date, ectopic parathyroid glands have not been described in literature as accompanying thymus removal due to myasthenia gravis.…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective, multicenter study included 54 patients with myasthenic crisis and, again, compared the efficacy of PE versus IVIG. 42 This trial pointed to a better tolerability and a shorter time of hospitalization for patients treated with IVIG. Yet, the need of artificial ventilation after 14 days was lower in patients receiving PE.…”
Section: Plasma Exchange In Multiple Sclerosis Relapsesmentioning
confidence: 91%
“…In a recent randomized study (114) with 66 patients with myasthenic crisis, intravenous immunoglobulin and plasma exchange were found to be equally effective. A multi-center chart review study to compare the efficacy and tolerance of plasma exchange and intravenous immunoglobulin in the treatment of episodes of myasthenic crisis has shown that both treatments were effective but plasma exchange was associated with higher complication rate compared with intravenous immunoglobulin (115). Juvenile myasthenia gravis has been treated with intravenous immunoglobulin and thymectomy (116).…”
Section: Myasthenia Gravismentioning
confidence: 99%